Strategic Management for Travel and Tourism - Evans, Nigel (Butterworth-Heinemann, 2015)
Strategic Management for Travel and Tourism is the must-have text for students studying travel and tourism. It brings theory to life by using industry-based case studies, and in doing so, 'speaks the language' of the Travel and Tourism student. Among the new features and topics included in this edition are: * international case studies from large-scale businesses such as Airtours, MyTravel and South West Airlines * user-friendly applications of strategic management theory, such as objectives, products and markets and strategic implementation, together with illustrative case studies, and longer case studies for seminar work and summaries * contemporary strategic issues affecting travel and tourism organizations, such as vertical integration and strategic alliances Strategic Management for Travel and Tourism is a well-rounded book, ideal for all undergraduate and postgraduate students focusing on strategy in travel and tourism. * Specifically written for the travel and tourism industry with strategic management applications and theory * Brings theory to life with industry-based case studies from Airtours, Marriott and Thomas Cook to enhance learning and understanding * Well rounded book which covers the contemporary strategic issues affecting travel and tourism organizations, such as cruising and 'all-inclusive' holidays.